USE OF ALOE VERA IN THE TREATMENT OF ORAL LICHEN PLANUS-A SYSTEMATIC REVIEW - RAMYA CHELLAMMAL MUTHUSAMY,; SREEDEVI DHARMAN. MDS, (International Journal of Pharma and Bio Sciences, 2016)
Oral lichen planus is a common, chronic mucosal disease associated with a cell-mediated immunological dysfunction. Symptomatic OLP is painful and complete healing is rare. Aloe vera has anti-inflammatory properties, its use as an herbal remedy in oral lichen planus is increasing. This systematic review aims in evaluating the use of Aloe Vera in the treatment of oral lichen planus. To determine the use of aloe vera in the treatment of oral lichen planus. The following electronic databases were searched namely PubMed(Mesh), Wiley online library, Cochrane Library using key words aloe vera and oral lichen planus. The total number of articles obtained are 27 (Wiley online library -5, Pub Med -17, Cochrane Library- 1, Hand search – 4) with preset inclusion and exclusion criteria to select the appropriate clinical trial. The search strategy included 5 potentially relevant articles for literature review. These randomized controlled trials reported that aloe vera is a well-tolerated, safe, effective alternative to corticosteroids with less side-effect in treating oral lichen planus. However there is weak evidence to support aloe vera in reducing pain and improving clinical signs of OLP compared to placebo. Even though the results in some of the studies were positive and promising, there was insufficient evidence to support the superior effectiveness of aloe vera in treating oral lichen planus.